When do employees feel isolated when working from home? Longitudinal trajectories, antecedents and outcomes of workplace isolation during the COVID-19 pandemic - Efimov, Ilona; Krick, Annika; Harth, Volker; Felfe, Jörg; Mache, Stefanie (Frontiers in Psychology, 2025)
IntroductionPrevious longitudinal studies investigated loneliness in general populations during the COVID-19 pandemic. Less is known about workplace isolation among employees working from home (WFH). Based on job demands-resources and conservation-of-resources theories, this study aims to analyze workplace isolation of employees WFH in relation to their WFH intensity.MethodsThis study examined the change in workplace isolation and WFH intensity over 5 measurement points of 512 employees using multilevel growth curve analysis (GCA), identified groups of participants with distinct trajectories of workplace isolation and WFH intensity using latent profile analysis (LPA), and investigated antecedents and consequences of profile membership.ResultsGCA indicated an overall negative linear and quadratic relationship between time and workplace isolation, as well as interaction effects between time and WFH intensity on workplace isolation. LPA identified 3 groups: (1) high WFH intensity and low isolation, (2) low WFH intensity and high isolation, (3) high WFH intensity and high isolation. Subsequent analyses revealed that individuals in profile 1 had high levels of health-oriented self-leadership (SelfCare) and social support by colleagues, and low levels of communication difficulties, health-oriented employee-leadership (StaffCare) and extraversion. Regarding differences, highest commitment was identified among individuals displaying low WFH intensity (profile 2), whereas highest self-rated performance was prevalent among individuals experiencing low workplace isolation (profile 1).DiscussionApplying GCA and LPA in this line of research is novel and adds to the understanding of both between-and within-effects of workplace isolation and WFH intensity. Knowledge about relevant resources (e.g., SelfCare) and demands (e.g., communication difficulties) may inform organizational practices aimed at preventing isolation in remote and hybrid work settings.